Heparan sulfates facilitate harmless amyloidogenic fibril formation interacting with elastin-like peptides - Federica Boraldi (Nature Portfolio, 2018)
Abstract Heparan sulfates (HSs) modulate tissue elasticity in physiopathological conditions by interacting with various matrix constituents as tropoelastin and elastin-derived peptides. HSs bind also to protein moieties accelerating amyloid formation and influencing cytotoxic properties of insoluble fibrils. Interestingly, amyloidogenic polypeptides, despite their supposed pathogenic role, have been recently explored as promising bio-nanomaterials due to their unique and interesting properties. Therefore, we investigated the interactions of HSs, obtained from different sources and exhibiting various degree of sulfation, with synthetic amyloidogenic elastin-like peptides (ELPs), also looking at the effects of these interactions on cell viability and cell behavior using in vitro cultured fibroblasts, as a prototype of mesenchymal cells known to modulate the soft connective tissue environment. Results demonstrate, for the first time, that HSs, with differences depending on their sulfation pattern and chain length, interact with ELPs accelerating aggregation kinetics and amyloid-like fibril formation as well as self-association. Furthermore, these fibrils do not negatively affect fibroblasts’ cell growth and parameters of redox balance, and influence cellular adhesion properties. Data provide information for a better understanding of the interactions altering the elastic component in aging and in pathologic conditions and may pave the way for the development of composite matrix-based biomaterials.